Strategic Leadership and Effective Management: Bridging the Gap Between TVET Curriculum and Industry Needs in Malaysia - Ab Halim, Fazlinda; Abdul Gani, Norsofea Aida (Journal of TVET and Technology Review, 2024)
Strategic leadership and effective management play crucial roles in ensuring that Technical and Vocational Education and Training (TVET) curricula remain aligned with industry needs. This alignment is essential for producing graduates equipped with the skills and knowledge required by employers, thereby enhancing employability and contributing to economic growth. This article presents a systematic literature review (SLR) of studies published between 2019 and 2024, focusing on the intersection of leadership, management, and TVET curriculum alignment in Malaysia. The review identifies key themes, challenges, and best practices, highlighting the importance of strategic leadership and effective management in bridging the gap between education and industry requirements.